Implications of Value Added Tax on Hosiery Industry of Ludhiana - Kumar, Babita; Banga, Gagandeep; Jain, Ketan (Indian Journal of Finance, 2008)
Ludhiana is the hub of hosiery industry comprising of large and small manufacturers. VAT had a powerful impact on all the hosiery manufacturers. This research paper attempts to find out the implications of VAT for these units. Primary data was collected from a randomly selected sample of 75 small-medium and 5 large hosiery units separately in proportion to their ratio in the total population. The result of the study shows that large units have seen a more uniform and favourable impact of VAT on their businesses whereas small-medium hosiery units have observed a mixed impact. However, the increasing impact on sales, profitability and tax liability is a good and healthy sign as it shows the growth in industry, but the increase in sale price, input cost, procedural formalities and paper work calls for a serious and immediate attention of the authorities. Hosiery units did face some problems in implementing VAT like lack of knowledge and awareness, no training, non-availability of C-forms etc. The VAT regime is perceived to curb tax evasion and to add more revenue to the state exchequer. But for this to happen VAT should be implemented in its totality and mindset of people must be changed.